Perluasan Akses Jaringan WiFi pada Umbul Siblarak untuk Meningkatkan Pendapatan Asli Daerah - Bebas Widada; Bayu Dwi Raharja; Andriani Kusumaningrum (Redtech Putra Benua, 2025)
Umbul Siblarak is a natural tourist destination with significant tourist potential. However, limited internet access hinders promotion, service delivery, and visitor data management. This community service initiative aims to expand WiFi network access in the Umbul Siblarak tourist area to support digital promotion, cashless transactions, and increase Regional Original Income (PAD). Implementation methods include site surveys, network topology design, device installation, system configuration, and manager training. Results show an 18% increase in visitor numbers within three months of installation, a 25% increase in digital transactions by MSMEs, and increased exposure of Umbul Siblarak on social media. This program significantly contributes to strengthening the local economy through the optimization of information technology.